TIME PERFORMANCE ANALYSIS ON AFV EARTHWORK IN KEDUNGPELUK SIDOARJO USING THE EARNED VALUE METHOD - Proboretno, Wuri; Witjaksana, Budi; Tjendani, Hanie Teki (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Construction project management has three main goals that must be achieved, namely cost, quality and time of work Plengsengan Afv. Kedungpeluk Sidoarjo which is planned to be completed within an estimated time of 120 calendar days and there are obstacles to contractor implementers who experience delays of 6.98% in this study researchers make efforts to find out Early Warning if there is poor performance in project completion so that management policies and changes in implementation methods can be made so that delays in project completion can be prevented.  Earned Value Method is used in the management of Afv Plengsengan work. Kedungpeluk Sidoarjo which will integrate the concept of time value. Earned Value Method is calculated from various factors that show the progress and performance of the project such as Schedule Variance (SV), work productivity index (CPI), time productivity index (SPI), and project completion schedule forecast (ECD), The results of using Earned Value Method get the results The amount of time required (ETS) at the end of the 8th week review is 91 days. While the time to complete the project (EAS) is 140 days. With this, the rate of change in project completion time is 0.16% longer, Based on the results of the analysis obtained for construction service providers who carry out development work, must apply good and efficient implementation methods in all stages of work with consistent supervision so that there is no delay in the construction work of Plengsengan Afv. Kedungpeluk Sidoarjo.